2020
DOI: 10.18805/lr-4434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Priming and Foliar Spraying of PGRs on Morpho-Physiology, Growth and Yield in Green gram (Vigna radiata L.)

Abstract: Background: Pre-sowing seed priming and foliar spraying with Plant Growth Regulators is an easy, low cost and low risk technique and also an alternative approach recently used to mitigate the effect of abiotic stresses in agricultural production.Methods: Seeds of Mung bean var. GAM-5 were primed and also foliar spraying at 30 DAS with CaCl2 2% and 1%, Cycocel 500, 1000 ppm, NAA 25, 50 ppm during summer season of 2015-16 and 2016-17.Result: The results indicated a significant improvement in morpho-physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It also increased the oil content significantly. Application of 1.3 per cent KCl at 45 and 60 DAS significantly increased seed cotton yield (Krishnaveni et al, 2004). Govindan and Thirumurugan (2000) observed that the foliar spray of KCl (1 per cent) + KNO 3 (1 per cent) increased the grain yield of green gram by 21.8 per cent.…”
Section: Role Of Potassium On Crop Growth and Stress Managementmentioning
confidence: 98%
See 1 more Smart Citation
“…It also increased the oil content significantly. Application of 1.3 per cent KCl at 45 and 60 DAS significantly increased seed cotton yield (Krishnaveni et al, 2004). Govindan and Thirumurugan (2000) observed that the foliar spray of KCl (1 per cent) + KNO 3 (1 per cent) increased the grain yield of green gram by 21.8 per cent.…”
Section: Role Of Potassium On Crop Growth and Stress Managementmentioning
confidence: 98%
“…Foliar application of nutrients at proper growth phases is essential for their consumption and improved crop performance (Krishnaveni et al, 2004). The presence of nutrients like Nitrogen, Phosphorus, Potassium, Sulphur and Magnesium are essential in balanced form for significant development processes of plants and yield production (Marimuthu and Surendran, 2015).…”
mentioning
confidence: 99%
“…Barry et al, 2007 [14] reported that anion exclusion processes dominate, NO 3 − ions are repelled from soil particle surfaces and move at a rate faster than the overall average pore-water velocity. Bhadane et al, [15] reported that seed priming with 2% CaCl 2 followed by 1% foliar spraying at 30 DAS significantly improved most of morpho-physiological parameters and yield contributing traits in Green gram. Seed treatment with bulk ZnSO 4 has produced higher total dry matter and grain yield but grain zinc content was highest in nano ZnO [11].…”
Section: Foliar Spraymentioning
confidence: 99%
“…Balusamy and Meyyazhagan [7] suggested that "the foliar application of nutrients was more appropriate, efficient and economical than soil application". "Application of nutrients on foliage at proper stages of crop growth plays an important role in utilization of nutrients and better performance of the crop" [8]. "Generally, Indian soils are rich in potassium but its availability to crops is low and not sufficient.…”
Section: Introductionmentioning
confidence: 99%